AYLANMA HARAKATDAGI BA'ZI ZARYADLAR TIZIMI MAGNIT MAYDONI INDUKSIYASINI HISOBLASH - Yavidov, B.; Kushboyeva, B.; Safarboyeva, F.; Abdullayev, E. (SCIENCE and SOCIETY, 2016)
The article deals with some problems on calculation of induction of the magnetic field induced by the system of charges performing rotational motion. It is assumed that the charges are distributed continuously and uniformly in the plane and space. The specific features of the system under consideration are given. In particular there are examples in the methods of calculation of induction of the magnetic field, induced by the uniformly distributed charges performing rotational motion in the disk, sphere and solid sphere. The methodical recommendations have universal character and allow to calculate magnetic field of complex systems.
Keywords: circular motion of charges; electric current; magnetic field; methods of solving a task